Kondisi sesaat kualitas air di sekitar kampus PSDKU IPB di Kota Sukabumi - Hefni Effendi; Mursalin Idris; Gatot Prayoga (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
This study aims to inform the initial data on water quality around the PSDKU IPB Sukabumi campus before the campus was built. Surface water is represented by the upstream, middle and lower reaches of the Cibeureum River. Residents' well water which represents the location of the planned construction of the PSDKU IPB campus in Sukabumi City, namely Babakan Village. Surface water quality parameters that do not meet the quality standards are BOD, COD, Nitrite, and Total Phosphate, while in well water quality, the parameter that does not meet the quality standards is Manganese (Mn). The pollution index indicates that the surface water quality is generally lightly polluted. For surface water, exceeding the quality standards of several parameters can be related to domestic waste and runoff from agricultural areas. The high value of Manganese in well water is a common phenomenon, which describes the natural characteristics of well water.